2009
DOI: 10.1002/pbc.21942
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial investigating an exercise program to prevent reduction of bone mineral density and impairment of motor performance during treatment for childhood acute lymphoblastic leukemia

Abstract: The exercise program was not more beneficial than standard care in preventing reduction in BMD, motor performance and passive ankle dorsiflexion than standard care, most likely due to unsatisfactory compliance. Increased BMI and body fat in the intervention group normalized faster after cessation of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
186
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(200 citation statements)
references
References 33 publications
6
186
1
7
Order By: Relevance
“…Twelve studies, [42][43][44][45][46][47][48][68][69][70][71][72] including two RCT 42,44 and seven high-quality studies [42][43][44][45][46]69,71 evaluated the effects of physical activity interventions on outcomes in children with pediatric cancer who did not undergo HSCT. One study of high quality 68 evaluated the effects of a single (30 min) exercise bout.…”
Section: Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies, [42][43][44][45][46][47][48][68][69][70][71][72] including two RCT 42,44 and seven high-quality studies [42][43][44][45][46]69,71 evaluated the effects of physical activity interventions on outcomes in children with pediatric cancer who did not undergo HSCT. One study of high quality 68 evaluated the effects of a single (30 min) exercise bout.…”
Section: Adultsmentioning
confidence: 99%
“…Despite improving fitness, interventions have not improved body composition. 42,70,72 As noted above, significant interest in the effects of exercise on blood markers exists for these patients. Marchese et al 69 reported no change in hemoglobin in ALL survivors (4-15 years) participating in aerobic and resistance training.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This shows the value of physical exercise, although we realize that it is a challenge to design such interventions sufficiently that it can be maintained for the full period of ALL treatment. 17 In summary, it still remains to be determined whether the definition of "adiponcosis" may survive over time as a clinical relevant entity, but we fully agree that the underlying mechanisms of adiposity as a risk factor for pediatric haematologica 2015; 100:e432 …”
mentioning
confidence: 84%
“…As a result, adult survivors of childhood cancer may suffer from cardiomyopathy, heart valve and conduction disorders [14,15], increased cardiovascular risk factors including hypertension, dyslipidemia [16][17][18], and obesity [19,20], pulmonary disorders [21,22], endocrine disorders [23] including hypothalamic-pituitary-adrenal disorders [24], diabetes mellitus [25], ovarian and Leydig cell dysfunction [26], and hypothyroidism [27]. Survivors of childhood cancer are also at increased risk for neurocognitive and neurosensory impairment including ocular degeneration, hearing loss and neuropathy [28][29][30][31], metabolic disturbances (abnormal blood counts, liver and kidney dysfunction, and osteoporosis) [28][29][30]32,33], transfusion-associated infections [30], and increased risk of subsequent neoplasm [14]. A major concern is that chronic LAE may increase in frequency and severity over time, and interact adversely with the normal ageing process, resulting in increasing and clinically significant impairment of vital organ systems during adulthood at a younger age than normal, and an increased risk of premature major illness or death [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%